Questioning 'The Authenticity of God Revelation' in Contemporary Quranic Reading: A Critical Review on Polemical Studies of Oriental and Liberal Scholars: [Menguji 'Otentisitas Wahyu Tuhan' Dengan Pembacaan Kontemporer: Telaah Atas Polemical Studies Kajian Orientalis dan Liberal] - Muzayyin Muzayyin (UIN Sunan Kalijaga Yogyakarta, 2014)
This paper deals with discourse trying to discuss various contemporary reading of the Koran, which is different from the classical understanding of the model. New research scholarship offered by the Quran in the form of structural linguistic approach is used to redefine the communication process between God with His chosen creature, using the frame of communication theory. The approach is then collaborated with the historical critical approach, which is one part of the methodology applied in Bible studies to the Qur’an. The emphasis is to clarify the origin of the source text focused on the origins of the Koran from the Judeo- Christian tradition. Furthermore, research with this approach seeks the historical aspects of the text of the Qur'an with the intention of reconstructing the historicity.[Diskursus dalam tulisan ini mencoba untuk mengurai berbagai pembacaan kontemporer terhadap al-Qur’an,yang berbeda dengan model pemahaman klasik. Riset baru yang ditawarkan oleh kesarjanaan Qur’an berupa pendekatan linguistic structural yang digunakan untuk memaknai ulang proses komunikasi Tuhan dengan mahluk pilihan-Nya, dengan bingkai teori komunikasi. Kemudian pendekatan itu dikolaborasikan dengan pendekatan kritik-historis,yang merupakan salah satu bagian dari metodologi Bibel yang diaplikasikan terhadap studi al-Qur’an. Fokusnya adalah untuk mengklarifikasi sumber asal usul teks, dengan menitikberatkan pencarian asal usul al-Qur’an dari tradisi Yahudi-Kristen. Melangkah lebih jauh, riset dengan pendekatan ini berusaha meneropong aspek kesejarahan teks al-Qur’an dengan maksud merekonstruksi ulang kesejarahannya.]